Analisis Faktor-Faktor yang Mempengaruhi Rasio Pembayaran Dividen pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Gayatri Kurnia Utami; Robin Robin (Jurnal Manajemen Maranatha, 2015)
This research aims to examine the factors that affect company’s dividend payout ratio in context of Indonesia. The object of this research are companies listed on Indonesia Stock Exchange (BEI) in the period from 2009 to 2013. The companiesused as a sample in this study is companies that regularly pay dividend for five years. This research used purposive sampling method, sample that meet the criteria are 20 firms or 100 observations data.The results of this study are firm size andprofitability is positive significant influence, cash flow is negative significant influence, and corporate tax, growth in sales, financial leverage, and market to book value is not significant.Keywords: Dividend Payout Ratio, Firm Size, Corporate Tax, Profitability,Market to Book Value, Growth Sales, Cash Flow, Financial Leverage